Rethinking transitional justice in sub-saharan Africa - (:unkn) unknown (My University, 2018)
Through a comparative study of different African conflicts, this research aims at underlying the need for complementarity between the different judicial and extra-judicial mechanisms of the transitional justice process. Sierra Leone, Central African Republic, Rwanda, Uganda, Darfur, Mozambique, every post-conflict situation has its own experience of Transitional Justice. There is no pre-conceived solution to solve a conflict, where the frontier between victims and perpetrators is constantly shaken, and with mass atrocities committed by both sides. Be it International Justice, National Justice, Truth and Reconciliation Commissions, or Local and Traditional Justice, none of these mechanisms of Transitional Justice can be efficient if they aren't any linkage between them and if they are not adapted to each specific contexts. For post-conflict justice to be a catalyst toward Reconciliation and a Sustainable Peace, peacemakers have to look deep into the political, the historical, and structural reasons that led to the commission of international crimes. The purpose of this PhD project is to encourage the adoption of a renewed plural vision of Justice in Africa, which would meet more specifically the needs of the war-torn population for a long-term peaceful society.
Keywords: African Research